Stimulating policy dialogue on the dry forests of Africa: a Sida/CIFOR initiative - Marunda, C.T.; Kowero, G.S.; Tiveau, D. (2004)
The purpose of this article is to introduce the dry forest programme and to highlight the importance of the progress to date